Preliminary Study on the Structure of Fungal Communities in Artificial Reef Areas in the Northern Yellow Sea - Jiamin Yan; Yue Yue; Shengkai Lin; Hanshitong Gu; Ziyi Han; Qingxia Li; Tao Tian; Xu Wei; Zhongxin Wu (Oceans)
The construction of artificial reefs is the primary ecological project of marine ranching and one of the most important methods of creating habitats for marine organisms. To date, studies on artificial reefs have taken a macroscopic perspective, with few studies having investigated the fungal communities in artificial reefs in the North Yellow Sea. Therefore, the aim of this study was to determine the distribution patterns of seawater quality, sediment properties, and fungal communities following the placement of artificial reefs of different materials in the North Yellow Sea. A sampling survey of marine ranching in the northern Yellow Sea was conducted in August 2023. Sediment and seawater samples were collected from the stone and concrete artificial reef areas as well as from the areas without constructed reefs as a control. Research shows that the total phosphorus (TP), total nitrogen (TN), and total organic carbon (TOC) concentrations were higher in the concrete reef than that in the other two regions. We obtained 735 fungal operational taxonomic units (OTUs) which were assigned to 11 phyla and 374 genera. Significant differences in the beta-diversity of the fungal communities were found among the three sampling regions, and the dominant species varied in seawater and sediment samples from different reef areas. Ascomycota was the most abundant phylum in the seawater and sediment samples, followed by Basidiomycota. pH and dissolved oxygen (DO) emerged as the most important factors affecting fungal communities in the seawater samples, whereas mean grain size, TN, and TOC had a significant effect on the communities in the sediments, with TP and TOC playing the most critical roles. Our study compared the characteristics of fungal communities in seawater and sediments in distinct types of artificial reefs and control areas, revealing the main environmental factors affecting fungal communities, which is of great significance for protecting biodiversity and evaluating the ecological effects of artificial reef placement.